The impact effect of county urbanization on rural revitalization and its spatial gradient in Northeast China - Jiaxin He; Liuqing Wei; Hui Kang; Ying Wang; Zixuan Zhao; Xiaohong Chen (Frontiers in Sustainable Food Systems, 2025)
Small towns play a vital role in the process of rural modernization and urban-rural integration in most developing countries. China's county urbanization is essentially based on small towns, and analyzing its role and patterns for rural development can provide scientific guidance for the practice of rural revitalization in China, as well as research results of typical regions for the theoretical study of urbanization and rural development in developing countries. Taking the 143 counties in Northeast China as examples, using Global Moran's I, OLS regression model, and Geographical and Temporal Weighted Regression(GTWR), analyzing the impact effect of urbanization on rural revitalization and its spatial gradient change in these counties from 2013 to 2020. The results show that: (1) County urbanization and rural revitalization in Northeast China show the evolution characteristics of “low volatility and decline” and “low and slow growth” respectively, and the statistical descriptive analysis of the superposition of the two spatial patterns preliminarily shows that county urbanization has some impact on rural revitalization. (2) The OLS model regression test shows that county urbanization in Northeast China is not enough to drive rural revitalization, there is still a lot of potential to be tapped. Among the selected 7 indicators of county urbanization, only the regression coefficient of X7 which represents the level of county education is as high as 0.5660. The regression coefficients of X2, X3 and X4, which related to the size of towns in county and the county economic strength, are all below 0.04. The level of healthcare development in county (X6) still acted as an obstacle to rural revitalization, while X1 and X5 do not pass the significance test. (3) The results of the GTWR model show that there is an obvious spatial gradient in the impact of the 5 indicators on rural revitalization in the county urbanization system in Northeast China. This study also proposes strategies to accelerate the construction of county urbanization in many ways in order to give full play to its positive effect on rural revitalization.